Application Of The 7E Learning Cycle Model To Students Learning Outcomes In Human Blood Circulation System Materials At Tgk Chiek Umar Diyan Junior High School - Nida Ulkhaira; Khairil Khairil; Wiwit Artika; Cut Nurmaliah; Hasanuddin Hasanuddin (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2021)
AbstractImproving learning outcomes can be done by increasing the quality of the learning process. One type of learning strategy that can be used to improve learning outcomes is the Learning Cycle. This model can improve the cognitive skills of students, nameIy learning outcomes. This study aims to see the appIication of the 7E Learning Cycle model can improve student learning outcomes in the human circulatory system material. The method in this study was an experimental design with a pretest-posttest control group design. The parameters used are the learning outcomes that were collected through the pre-test and post-test. The data obtained were tabulated and analyzed with the N-Gain formula to see an increase in the score. Independent sample t-test was conducted to see the difference in the learning outcomes of students in the experimental class and the control class. The results of the independent sample t-test for the learning outcomes of male students, obtained tcount = 7.55 ttable = 1.67 (Mean = 85.61. SD = 5.30). And for the female class, obtained tcount 5.29 ttable 1.67 (Mean = 86.39. SD = 5.32). So it can be ignored that the 7E Learning Cycle model can improve student learning outcomes in the human circulatory system material.Keywords: Learning Cycle 7E, Learning Outcomes, Oemar DiyanAbstrakPeningkatan hasil belajar dapat dilakukan dengan meningkatkan kualitas proses belajar. Salah satu jenis strategi pembelajaran yang dapat digunakan untuk meningkatkan hasil belajar adalah siklus belajar (Learning Cycle). Pada dasarnya model ini dapat meningkatkan keterampilan kognitif peserta didik yaitu hasil belajar. Penelitian ini bertujuan untuk mengetahui penenerapan model Learning Cycle 7E dapat meningkatkan hasil belajar peserta didik pada materi sistem peredaran darah manusia. Metode dalam penelitian ini adalah eksperimen berdesain pretest-posttest controlIgroup desain. Parameter yang digunakan yaitu hasil belajar belajar yang dikumpulkan melalui pre-test dan post-test. Data yang diperoleh ditabulasi dan dianalisis dengan rumus N-Gain untuk mengetahui peningkatan skor. Uji independent sample t-test dilakukan untuk mengetahui perbedaan skor hasil belajar peserta didik kelas eksperimen dan kelas kontrol. Hasil uji independent sample t-test untuk hasil belajar kelas peserta didik laki-laki, diperoleh thitung = 7,55 ttable = 1,67 (Mean= 85,61. SD= 5,30). Dan kelas peserta didik perempuan, diperoleh thitung 5,29 ttable 1,67 (Mean= 86,39. SD=5,32). Sehingga dapat disimpulkan bahwa penerapan model Learning Cycle 7E dapat meningkatkan hasil belajar peserta didik pada materi sistem peredaran darah manusia.Kata  Kunci:  Learning Cycle 7E,  Hasil Belajar, Oemar Diyan